Further Odd-Even Sum Labeling Graphs - K. Monika; K. Murugan (International Journal of Mathematics And its Applications, 2017)
A $(p,q)$ graph $G=(V,E)$ is said to be an odd-even sum graph if there exists an injective function $f:V(G)→\lbrace± 1,± 3 ± 5, ...,± (2p-1)\rbrace$ such that the induced mapping $f^{*}:E(G)→\lbrace 2,4,6, ...,2q\rbrace$ defined by $f^{*}(uv)=f(u)+f(v)~\forall~uv\in E(G)$ is bijective. The function $f$ is called an odd-even sum labeling of $G$. In this paper, odd-even sum labeling of subdivision of star $K_{1,n}(n≥ 1)$,Subdivision of bistar $B_{m,n}$,and H-graphs are studied.